Penerapan Keadilan Restoratif dalam Penyelesaian Tindak Pidana Kekerasan dalam Rumah Tangga di Wilayah Hukum Polrestabes Medan Tahun 2022 - 2024 - Fitri, Desi Ira Ari; Nasution, Rasina Padeni (Universitas Muhammadiyah Ponorogo, 2025)
Criminal case settlement can be done in two ways, namely litigation (through the trial process in court) and Non-litigation (outside the court). The non-litigating method is currently known as Restorative Justice. Restorative Justice can be applied in minor crimes including Domestic Violence (KDRT). In response to the large number of domestic violence cases reported in the jurisdiction of the Medan Police, Restorative Justice was applied as an effort to resolve the crime of domestic violence. Based on Perpol No. 8 of 2021, the police have a significant role in applying the principles of Restorative Justice in resolving domestic violence cases. This study aims to examine the application of Restorative Justice in the resolution of domestic violence crimes as well as the challenges and obstacles experienced by the Medan Police Department. The type of research used is empirical juridical research and uses a case approach. The data source in this study is the primary data source obtained from the field by interviewing the Medan Police Department, then the data analysis technique used is qualitative analysis. The result of this study is that the Medan Police apply the principle of restorative justice in resolving domestic violence cases by facilitating dialogue between the perpetrator and the victim in a professional, neutral manner and ensuring that the victim does not experience intimidation and feel pressured by ensuring that the victim can voice what he feels and what impact he experiences as a result of the violence committed by the perpetrator. The victim is compensated for the losses he has suffered. In implementing restorative justice, the Medan Police did not find any challenges, but there were obstacles experienced by the police, namely incitement from other parties such as family and others, thus hindering the implementation of restorative justice.